Kajian Yuridis Putusnya Perkawinan Akibat Cerai Gugat - Yolanda Tresna Dian A; Saharuddin Saharuddin; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2023)
This study aims to find out the legal considerations of judges in deciding a marriage due to divorce in the Religious Court of Parepare City (Case Study Number 123/Pdt.G/2022/PA.Pare). Parepare City Religion. This research uses a normative research type supported by a statutory approach and a case study approach, the types and sources of data using primary data, secondary data, tertiary data, and data analysis are examined qualitatively and descriptively. The results of the study show that the judge's legal considerations in breaking up a marriage due to divorce were sued at the Parepare Municipal Religious Court Number 123/Pdt.G/2022/PA.Pare is correct and correct, where the basis for the judge's consideration is that the plaintiff and the defendant have separated residence for 6 years and 8 months until now the plaintiff left the place shared residence and since the house separated between the plaintiff and the defendant there has been no communication and no visiting each other and there is no maintenance from the defendant to the plaintiff, that during the trial, the plaintiff was determined to separate from the defendant, and the factors that led to the breakup of the marriage due to divorce sued in Parepare City Religious Court, namely: Internal factors, namely economic factors, not being given a living, disputes and constant bickering, external factors, namely the factor of infidelity or the presence of other ideal women, the interference of parents and drunkards or gamblers.